THE ROLE OF EDUCATION IN ENHANCING CITIZENS' LEGAL CULTURE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The presented article analyzes the role and importance of the education system in the process of enhancing citizens' legal culture, examining the main components of legal culture – legal knowledge and skills, respect for and compliance with laws, legal responsibility and beliefs. The provision of legal education in schools and higher education institutions, increasing legal literacy through mass media and the internet, and the activities of state and public organizations are widely discussed. The necessity of improving educational programs, using interactive methods, and providing legal education in families is substantiated as ways to enhance the effectiveness of legal education.